If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying z + 6 = -5 Reorder the terms: 6 + z = -5 Solving 6 + z = -5 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + z = -5 + -6 Combine like terms: 6 + -6 = 0 0 + z = -5 + -6 z = -5 + -6 Combine like terms: -5 + -6 = -11 z = -11 Simplifying z = -11

| x(x)-5x+53=119 | | z+12=-19 | | 4x(x+4)=0 | | 6x^3-24=0 | | 18x(x)(x)=50x | | x(x)+12x+36=25 | | 5x^2-44x+63=0 | | 4x^2+8x+27=0 | | x+3=-15 | | m+-3=9 | | c+22=-27 | | v-18=-4 | | m+33=16 | | 55+-21= | | 55+-21=m | | x^3-12x-25=0 | | 4(-X-5)=-3 | | 4x-7=8x-2x | | 15x+4y+12=152 | | 2z=-4 | | 5x+5=-10x | | 5x+5=-145-10x | | 10-7x=126-35x | | 101-6x=39x+21 | | x-5=3(2-2x) | | 6x+38=14x-42 | | 2n+239=12n-11 | | 3(1-x)-4=7-2x | | x^2=8+6i | | a*a= | | 21-6x=(-11)-14x | | 0.03*(1156.01+x)=x | | 15x^2-13x-2=0 | | 19-x=10 | | 3x+6=9x-6 | | p-8+6=15 | | 5x+12=4x+7 | | y-8+7=3 | | (4r-7)-(3r+12)=0 | | 9+4x=5x+18 | | 4m^3-1= | | 10(x+80)+.20x+2=10+.30x | | 16-3b=22 | | a-5-3=12 | | 5g+8=33 | | 7(-4+3)+4=3 | | 12y=6x-12 | | 22-(3+x)=(x+4) | | 0.05x=-55 | | -x^2+2x=-8-10x | | s-4=7 | | W^2-9=0 | | X^2-16=-8x | | X^2-169=0 | | X^2*3x-54=0 | | 5x(x+2)=0 | | A^2+64=-16a | | 2x+37=5x+13 | | -3x=63 | | -2x+5=-27 | | 27+15x-6x^2=0 | | 7x+6=4x-7 | | 6x-3=24x+9 | | 4x+5=5x | | 7x+6=4(x-7) |